The roots run deep?: Understanding branch politics within the African National Congress - Mkhutle, Nhlanhla Handsome (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This thesis explores the functioning of branch politics within the African National Congress (ANC) and the influence of branch politics on the organization and its structures. The ANC has many of the characteristics of a mass party. In mass parties, mass participation is supposed to be promoted through the activities of party branches. This thesis documents the weakening of the ANC's local level structures and their political control over the organization's decisions. ANC branches are investigated as democratic vanguards of ANC's mass party persona, in relation to their functioning as the most basic units of the organization. The thesis reflects on branch members' experiences in different ANC branches to understand the interplay between branch politics, political power, and patronage politics within the ANC. This research project also explores the possibility of manipulation of ANC branches by senior leaders and would-be-leaders of the ANC. The thesis then concludes by summarising the state of branch politics within the ANC and giving recommendations on further study with regards to branch politics of the ANC.
Keywords: African National Congress; Manipulative behavior Political aspects -- South Africa; Cartels -- South Africa; Power (Social sciences) -- South Africa; Patronage, Political -- South Africa; Political party organization -- South Africa; Branch politics